Identification of candidate loci for adaptive phenotypic plasticity in natural populations of spadefoot toads. Issue 16 (24th July 2020) - Levis, Nicholas A.; Reed, Emily M. X.; Pfennig, David W.; Burford Reiskind, Martha O.
Abstract: Phenotypic plasticity allows organisms to alter their phenotype in direct response to changes in the environment. Despite growing recognition of plasticity's role in ecology and evolution, few studies have probed plasticity's molecular bases—especially using natural populations. We investigated the genetic basis of phenotypic plasticity in natural populations of spadefoot toads ( Spea multiplicata ). Spea tadpoles normally develop into an "omnivore" morph that is favored in long‐lasting, low‐density ponds. However, if tadpoles consume freshwater shrimp or other tadpoles, they can alternatively develop (via plasticity) into a "carnivore" morph that is favored in ephemeral, high‐density ponds. By combining natural variation in pond ecology and morph production with population genetic approaches, we identified candidate loci associated with each morph (carnivores vs. omnivores) and loci associated with adaptive phenotypic plasticity (adaptive vs. maladaptive morph choice). Our candidate morph loci mapped to two genes, whereas our candidate plasticity loci mapped to 14 genes. In both cases, the identified genes tended to have functions related to their putative role in spadefoot tadpole biology. Our results thereby form the basis for future studies into the molecular mechanisms that mediate plasticity in spadefoots. More generally, these results illustrate how diverse loci might mediate adaptive plasticity. Abstract : By combining natural variation in pond ecology and ecomorph production with population genetic approaches, we identified candidate loci associated with morph (carnivores vs. omnivores) and loci associated with adaptive phenotypic plasticity (adaptive vs. maladaptive morph choice) in spadefoot toad tadpoles. We identified 16 candidate genes that tended to have functions related to their putative role in spadefoot tadpole biology, and most of these genes were associated with adaptive plasticity rather than morph.